2021
DOI: 10.1029/2020jc016146
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Controls on Sediment Delivery and Hydrodynamics in a Vegetated Tidally Influenced Interdistributary Island

Abstract: River deltas are among the world's most imperiled landscapes. Their low elevations, combined with their typically low elevation gradients, make them particularly vulnerable to changes in sediment supply, eustatic sea-level rise (Cazenave & Llovel, 2010) and subsidence (Erickson, 2006), as their sustainability largely hinges on the relative balance between these factors (Syvitski, 2008). With over 500 million people

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Yet, even without the confirmation of detailed chemical analysis, this seasonal shift in SE‐channel turbidity coupled with the seasonally consistent import suggest that sediment resuspended from the clinoform or transported from nearby river systems can be deposited on land surfaces. Coastal sediment recycling has been observed in other well‐studied deltas such as the Mekong in Vietnam (Fricke et al ., 2017), Ganges‐Brahmaputra in Bangladesh (Rogers et al ., 2013; Hale et al ., 2019) and Wax Lake in the USA (Styles et al ., 2021). This recycling increases the short‐term capacity for the subaerial delta to keep pace with sea‐level rise (Yang et al ., 2020), at least until the submarine delta is depleted (Nienhuis et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, even without the confirmation of detailed chemical analysis, this seasonal shift in SE‐channel turbidity coupled with the seasonally consistent import suggest that sediment resuspended from the clinoform or transported from nearby river systems can be deposited on land surfaces. Coastal sediment recycling has been observed in other well‐studied deltas such as the Mekong in Vietnam (Fricke et al ., 2017), Ganges‐Brahmaputra in Bangladesh (Rogers et al ., 2013; Hale et al ., 2019) and Wax Lake in the USA (Styles et al ., 2021). This recycling increases the short‐term capacity for the subaerial delta to keep pace with sea‐level rise (Yang et al ., 2020), at least until the submarine delta is depleted (Nienhuis et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These deviations in salinity were either driven by salt exchange with groundwater or long residence times of previously imported water from the river, as they would not be produced by the seasonal rainfall patterns. Similarly, in the microtidal Wax Lake Delta, intra‐island residence times for water were significantly greater than those in adjacent channels (Hiatt & Passalacqua, 2015; Hiatt et al ., 2018) and substantially altered deltaic fluxes of nutrients (Styles et al ., 2021). These observations in Meinmahla Island demonstrate that there are comparably long intra‐island residence times in ME channels of a macrotidal environment.…”
Section: Discussionmentioning
confidence: 99%
“…Wetland vegetation has a strong influence on sediment transport in river deltas 13 , 14 . It is widely believed that vegetation enhances sedimentation in both fresh- and saltwater marshes as vegetation increases hydraulic roughness, which reduces flow velocity 15 , enhancing sediment retention, stabilizing deposited sediment, and minimizing erosion 16 , 17 However, some field observations and numerical models have shown that vegetation does not always enhance sedimentation on deltaic marshes 13 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on typical conditions in marshes 18 – 21 , 16 base cases considered vegetation area density n = 0 to 500 stems/m 2 , with stem diameter d = 1.0 cm, water depth H = 0.3 m, and water surface slope S = 0.0005. To consider seasonal effects on vegetation growth and water flux 14 , additional slopes ( S = 0.00025 and 0.001) and stem diameters ( d = 0.5 and 1.5 cm) were considered, for a total of 80 cases. Finally, the model was compared to a field study within the MRD, reported in ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods rely on elevation maps acquired months to years apart, making it impossible to mechanistically link specific hydrodynamic or environmental conditions to bathymetric change. Bathymetric change is sensitive to a variety of factors, including floods, cold fronts, hurricanes, tides, wind, and vegetation (Bevington et al, 2017;Carle et al, 2015;Styles et al, 2021). Remote-sensed synoptic measurement of deposition and erosion would provide a way to directly link specific processes to resulting patterns of bathymetric evolution.Several studies have derived relationships between suspended sediment concentration (SSC) and remotely-sensed spectral radiance in order to generate maps of SSC (Curran & Novo, 1988;Peckham, 2008;Van der Wal et al, 2010).…”
mentioning
confidence: 99%